The Effect of Market Ratio and Profitability Ratio on Stock Return (Survey on the Hotel Industry on the Indonesia Stock Exchange, 2018-2022) - Nurjaman, Agis; Yusnita, Rita Tri; Wibawa, Gian Riksa (Journal of Management, Economic, and Accounting, 2024)
This study aims to determine the effect of Market Ratio and Profitability Ratio on Stock Return in the Hotel Industry on the Indonesia Stock Exchange during the period 2018-2022. This research uses a correlational research method with a quantitative approach. The data used is secondary data, with a research sample of 10 hotel companies listed on the Indonesia Stock Exchange using Purposive Sampling. The data analysis tool used is panel data regression analysis, and the hypotheses are tested using F-tests and t-test with a significance level of 5%. The results of the regression analysis show that simultaneous test show that all independent variables simultaneously do not have a significant effect on Stock Return. The results of the partially both PER and ROA variables do not have a significant effect on Stock Return.